Productive performance and reproductive characteristics of Morada Nova male lambs fed with high-energy diet - Barreto, Andrea do Nascimento (2019)
Morada Nova breed sheep are without wool, tropicalized, small-sized animals, known for their high-quality meat and skin. Their body development naturally depends on the genetic potential and adequate nutritional support, which suggests that the offer of high-energy density diets positively influences their productive indicators. Thus, the present study investigated the effect of a high-energy diet for the Morada Nova lambs on body development and testicular function, considering their histomorphometric characteristics and seminal quality. Forty-two males (19.2 weeks, 20.7 +/- 3.5 kg) were equally divided into two groups and fed with 2.05 Mcal (G7, n=21) or 2.37 Mcal (G24, n=21) of metabolizable energy/day, equivalent to 7% and 24% above the minimum for growing lambs. The animals were confined for 23 weeks (W0 to W23). Weight and body score differed significantly from the W1 (P<0.05). From the W5, thoracic perimeter, body length, wither height, and rump attributes were higher in G24 (P<0.05). The scrotal circumference and testicular volume were higher in G24 from the W3 (P<0.05). Although testosterone levels were not affected (P =0.05), the highest energy intake increased the diameter of the seminiferous tubules and the development of the epididymal epithelium (P<0.05). This positively influenced the seminal quality and reduced the minor defects (21.87% vs. 17.13%) and the total spermatic defects (26.34% vs. 21.78%, P<0.05). Thus, it is possible to employ higher levels of dietary energy for Morada Nova young males to express higher productive efficiency and earlier reproductive attributes of interest.